473 INTRAUTERINE GROWTH RESTRICTION Affects Hepatic Androgen Receptor Expression and TestostERone Levels in Juvenile Rats. (1st January 2006) - Contreras, Y.; McKnight, R. A.; Yu, X.; Callaway, C. W.; Lane, R. H.
Abstract : Background: Uteroplacental insufficiency and subsequent IUGR results in multiple postnatal morbidities, the extent of which is often affected by gender. Similarly, we have previously demonstrated that gender impacts upon the extent to which IUGR affects hepatic gene expression and epigenetic determinants of chromatin structure. One mechanism through which epigenetic determinants can be altered is through signaling via the androgen and estrogen receptors, which are likely to be different in male and female rats. Objective: We therefore hypothesized that IUGR would (1) affect testosterone and estrogen levels in 21-day-old rats (d21) and (2) alter hepatic mRNA levels of the androgen receptor (AR), estrogen receptor 1 (ER1), and estrogen receptor 2β (ER2β) in day 0 (d0) and d21 IUGR rats. Methods: We rendered rats IUGR via bilateral uterine artery ligation at day 19 of gestation (term-21.5 d), a well-characterized model of IUGR. D0 pups were delivered by cesarean section at d21 of gestation. D21 pups were allowed to delivery, litters were culled to 6, and pups were killed at d21 of life. Liver was harvested at d0 and d21 for mRNA measurements. Serum was harvested at d21 for hormone levels. Results: We found that IUGR significantly increased testosterone levels in the IUGR female rats (16.5 ± 1* vs 14 ± 0.3 pg/mL) and moderately increased testosterone levels in the IUGR male rats (26.3 ± 6.5 vs 19.3 ± 1.7 pg/mL). Estrogen levels were not significantly affected by IUGR. mRNA data expressed as percent of control ± SEM. IUGR significantly increased AR mRNA levels in d0 male livers (146 ±±18%*) without affect AR mRNA levels in d0 female livers. ER1 mRNA levels were significantly increased in d0 female livers (208 ± 37%*), and ER2B mRNA levels were significantly increased in d0 male (289 ± 33%*) and female livers (123 ± 8%*). In contrast, at d21 of life, IUGR decreased hepatic AR mRNA levels only in the male livers (36.3 ± 2.8%**). AR, ER1, and ER2B mRNA levels were otherwise not statistically affected. (* p < .05; * p < .01) Conclusion: IUGR increases postnatal androgen levels in juvenile female pups, while decreasing AR mRNA levels only in the male IUGR livers. AR signaling affects gene expression through multiple mechanisms, including epigenetics. We speculate that the failure of the IUGR female to down-regulate its AR contributes to the gender-specific characteristics of the IUGR rat.